Design, Synthesis and Docking Studies of Flavokawain B Type Chalcones and Their Cytotoxic Effects on MCF-7 and MDA-MB-231 Cell Lines - Addila, Abu Bakar; Akhtar, Muhammad Nadeem; Norlaily, Mohd Ali; Swee, Keong Yeap; Ching, Kheng Quah; Wan-Sin, Loh; Noorjahan Banu, Alitheen; Seema, Zareen; Ul-Haq, Zaheer; Syed Adnan, Ali Shah (MDPI - Open Access Publishing, 2018)
Flavokawain B (1) is a natural chalcone extracted from the roots of Piper methysticum, and has been proven to be a potential cytotoxic compound. Using the partial structure of flavokawain B (FKB), about 23 analogs have been synthesized. Among them, compounds 8, 13 and 23 were found in new FKB derivatives. All compounds were evaluated for their cytotoxic properties against two breast cancer cell lines, MCF-7 and MDA-MB-231, thus establishing the structure–activity relationship. The FKB derivatives 16 (IC50 = 6.50 ± 0.40 and 4.12 ± 0.20 μg/mL), 15 (IC50 = 5.50 ± 0.35 and 6.50 ± 1.40 μg/mL) and 13 (IC50 = 7.12 ± 0.80 and 4.04 ± 0.30 μg/mL) exhibited potential cytotoxic effects on the MCF-7 and MDA-MB-231 cell lines. However, the methoxy group substituted in position three and four in compound 2 (IC50 = 8.90 ± 0.60 and 6.80 ± 0.35 μg/mL) and 22 (IC50 = 8.80 ± 0.35 and 14.16 ± 1.10 μg/mL) exhibited good cytotoxicity. The lead compound FKB (1) showed potential cytotoxicity (IC50 = 7.70 ± 0.30 and 5.90 ± 0.30 μg/mL) against two proposed breast cancer cell lines. It is evident that the FKB skeleton is unique for anticancer agents, additionally, the presence of halogens (Cl and F) in position 2 and 3 also improved the cytotoxicity in FKB series. These findings could help to improve the future drug discovery process to treat breast cancer. A molecular dynamics study of active compounds revealed stable interactions within the active site of Janus kinase. The structures of all compounds were determined by 1H-NMR, EI-MS, IR and UV and X-ray crystallographic spectroscopy techniques.